2005
DOI: 10.1002/glia.20267
|View full text |Cite
|
Sign up to set email alerts
|

Differential oxidative stress in oligodendrocytes and neurons after excitotoxic insults and protection by natural polyphenols

Abstract: Oligodendrocytes are vulnerable to overactivation of both their AMPA receptors and their high-and low-affinity kainate receptors. Depending on the intensity of the insult and the type of receptor activated, excitotoxic oligodendrocyte death mediated by these receptors has different characteristics. One important consequence at a cellular level is the ensuing oxidative stress, related to Ca 21 -dependent alterations in mitochondrial functioning. We observed that oxidative stress associated with selective AMPA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…Consistent with this, ebselen, which is an efficient scavenger of peroxynitrite as well as a gluthione peroxidase mimic, prevented noise-induced swelling of the auditory nerve dendrites (Yamasoba et al, 2005). Antioxidants also reduce glutamate-induced toxicity in other neural systems (Matteucci et al, 2005;Tastekin et al, 2005;Ibarretxe et al, 2006).…”
Section: Glutamate Excitotoxicitymentioning
confidence: 55%
“…Consistent with this, ebselen, which is an efficient scavenger of peroxynitrite as well as a gluthione peroxidase mimic, prevented noise-induced swelling of the auditory nerve dendrites (Yamasoba et al, 2005). Antioxidants also reduce glutamate-induced toxicity in other neural systems (Matteucci et al, 2005;Tastekin et al, 2005;Ibarretxe et al, 2006).…”
Section: Glutamate Excitotoxicitymentioning
confidence: 55%
“…Thus, we propose that morin maintains nigrostriatal pathway function by enhancing the survival of dopaminergic neurons in MPTP-lesioned mice. Besides the antioxidant activity that we detected in the in vitro model, the anti-inflammatory activity of morin may also contribute to its neuroprotective effects in vivo [12,31] . In conclusion, the present study indicates that morin has robust neuroprotective properties.…”
Section: Discussionmentioning
confidence: 71%
“…Morin (3,5,7,2',4'-pentahydroxyflavone, Figure 1) is a natural bioflavonoid that was originally isolated from members of the Moraceae family and is a constituent of many herbs, fruits and wine. Previous studies have shown that morin exerts antioxidant, anti-inflammatory, and antiproliferative effects in vivo and in vitro [11][12][13] . Studies investigating the neuroprotective effects of morin have been inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, within the concentration range of the compound used, there was no observed toxicity on the cultured cells as indicated by initial studies of the compound by cell viability assays. Also, morin has been used on other cultured cells and no cytotoxic effects have been reported (Wu et al, 1994;Zeng et al, 1998;Mazzio et al, 2001;Ibarretxe et al, 2006). As for the three positive controls, they all showed inhibitory actions in the uptake assay.…”
Section: Discussionmentioning
confidence: 99%